THE USE OF KNOW- WANT TO KNOW- LEARNT STRATEGY FOR TEACHING HORTATORY EXPOSITION READING COMPREHENSION - Astriana, Lidia; Supardi, Iwan; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research was to investigate whether the students’ achievement in reading comprehension on hortatory exposition text increases significantly when it was taught by using KWL strategy. This was a pre- experimental research with one group pre-test and post-test design. The participant of this research was students in eleventh grade spesifically class AKL 3 of SMK Negeri 1 Pontianak in Academic Year 2018/2019. There were 36 students who participated in this research. The data had been collected by using measurement technique. The tools of data collection was multiple choice tests. The data were calculated and the result showed that the mean score of students’ pre-test was 53.05 while the post-test was 84.30. the different score between pre-test and post-test was 31.25. Based on the research finding the null hypothesis (H0) was rejected while alternative hypothesis (Ha) was accepted. The calculation of the t-test showed that the t-ratio was higher than the t value (4.690> 2.021) at a degree of freedom (df) = N- 1 (36-1) and at 95% of confidence (p= 0.05). To conclude, the use of KWL Strategy was significant and effective to teach hortatory exposition reading comprehension to the eleventh grade students of SMK Negeri 1 Pontianak in Academic Year 2018/2019. Keywords : KWL Strategy, Pre-Experimental Research, Reading Comprehension